2005
DOI: 10.1159/000087366
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Length of Hospital Stay in Patients with Bacterial Pleural Effusion

Abstract: Background: Factors influencing length of hospital stay have been poorly analyzed in parapneumonic pleural effusions (PPE). Objectives: The aim of this work is to identify the variables that determine increased hospital stay in patients with infectious pleural effusion (PE). Patients and Methods: We analyzed 112 patients with PE: empyema, complicated parapneumonic and non-complicated parapneumonic. Epidemiologic, biochemical, therapeutic and radiological variables were analyzed. Correlations with hospital stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The negative CR group had significantly lower incidences of complicated parapneumonic effusion or empyema and pleural drainage than the control group. Previous studies have suggested that complicated parapneumonic effusion or empyema could prolong the LOS in hospitalized CAP patients [23, 24]. This can partly explain the shorter LOS in the negative CR group in our study.…”
Section: Discussionsupporting
confidence: 53%
“…The negative CR group had significantly lower incidences of complicated parapneumonic effusion or empyema and pleural drainage than the control group. Previous studies have suggested that complicated parapneumonic effusion or empyema could prolong the LOS in hospitalized CAP patients [23, 24]. This can partly explain the shorter LOS in the negative CR group in our study.…”
Section: Discussionsupporting
confidence: 53%
“…11,12 There are some patients for whom initial treatment is not possible and in whom chronic empyema will develop, mainly due to delayed diagnosis or late referral. At this stage, the standard treatment is open thoracotomy and decortication.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, the standard treatment is open thoracotomy and decortication. Historically, other surgical procedures have been practiced, including open window thoracotomy, rib resection, thoracoplasty, Claggett's procedure and percutaneous drainage guided by ultrasound or CT. [11][12][13] With the increasing popularity of minimally access surgery, video-thoracoscopy has been proposed for the treatment of chronic empyema. 13 There are reports in which open procedures have shown higher morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that pleural empyema should be treated early to avoid complications, extensive operations and lengthy hospital stays. 6, 16 Unfortunately, there are some patients for whom early treatment is not possible and in whom chronic empyema will develop, mainly due to delayed diagnosis or delayed referral. At this stage, the standard treatment is open thoracotomy and decortication.…”
Section: Discussionmentioning
confidence: 99%